Novel clinical applications of extracellular vesicles - Matias Saenz-Cuesta (Frontiers Research Topics, 2015)
During the last years, the research on extracellular vesicles (EVs) has raised giving new insights into pathophysiology of several diseases. EVs are membrane-bound particles secreted by almost all cell types. Depending on their biogenesis and size they include exosomes, microparticles / microvesicles and apoptotic bodies. Characteristically, EVs carry markers from the source cell membrane and contain genetic material, lipids and proteins inside. They are known to play a role in cell-to-cell communication and to produce genotypic and phenotypic modifications in the target cell including: antigen presentation, apoptosis induction, cellular activation, inhibition or differentiation. In particular, increasing concentrations of EVs have been found in many diseases such as cancer, autoimmune and cardiovascular diseases, among others. Most of the studies in EVs are focused on the characterization of EVs compounds, identifying mechanism of action, their potential use as biomarkers, and few of them investigate a therapeutic usage. However, there are some issues to be achieved on the path to their clinical application. This research topic offers a common place to discuss current and novel clinical applications of EVs pointing on future directions. We encouraged the submission of original articles, reviews, hypothesis, controversies, future perspectives and personal viewpoints on the following topics of interest, but not limited to: • Contribution of EVs to better understand the pathology of immunological diseases. • Standardization of isolation and quantification protocols in the daily clinical practice. • Possible applications of EVs as clinical biomarkers (diagnostic, prognostic and evolution marker). • Therapeutic role of EVs being vehicles of specific cargo: current clinical trials? • Novel immunological functions of EVs.